2020
DOI: 10.3390/agronomy10111707
|View full text |Cite
|
Sign up to set email alerts
|

Tapping the Economic Potential of Chickpea in Sub-Saharan Africa

Abstract: Chickpea is a nutrition-rich, cropping-system friendly, climate-resilient, and low-cost production crop. It has large economic potential in the sub-Saharan Africa (SSA) region, where it currently accounts for only approximately half a million hectares of the approximately 12 million hectares of total chickpea production land worldwide. This review highlights the opportunities for promoting chickpea production and marketing to tap the vast economic potential in SSA. The region can potentially produce chickpea o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…Southeastern Turkey and adjoining Syria are the primary Vavilovian centers of origin, and Ethiopia is the secondary center of diversity [2,3]. In Ethiopia, chickpea is one of the most economically important legumes produced on an area of 258,486 ha, with a production of 470,000 tons [4][5][6]. Ethiopia is one of the top ten chickpea growing countries across the world and is the leading producer, consumer, and exporter of chickpeas in Africa [7].…”
Section: Introductionmentioning
confidence: 99%
“…Southeastern Turkey and adjoining Syria are the primary Vavilovian centers of origin, and Ethiopia is the secondary center of diversity [2,3]. In Ethiopia, chickpea is one of the most economically important legumes produced on an area of 258,486 ha, with a production of 470,000 tons [4][5][6]. Ethiopia is one of the top ten chickpea growing countries across the world and is the leading producer, consumer, and exporter of chickpeas in Africa [7].…”
Section: Introductionmentioning
confidence: 99%
“…India and Ethiopia have been proposed as secondary centers of diversity for cultivated chickpea [8]. Based on the presence of wild relative (Cicer Cuneatum) found in Northern Ethiopia [9] and the Archaeological evidence from Lalibela caves in Ethiopia with seed samples with seed sample dated at over 2500 years [10], Fikre et al [11] suggested for reconsideration of Ethiopia as the origin of chickpea. However, with the current consensus, Ethiopia is considered as the secondary center of diversity for chickpea [8].…”
Section: Introductionmentioning
confidence: 99%
“…Because, it serves as a cash crop, break crop for crop diseases managements, a rotational crop for soil fertility restoration, food for human beings, and feed for animals. It is also suitable for sustainable agriculture production system with little or no climatic shocks [11]. In Ethiopia, chickpea is the third largest food legume crop in sowing area and production and the second major export commodity next to white pea beans generating nearly 25% of the total legumes export earnings [13].…”
Section: Introductionmentioning
confidence: 99%
“…L) is an important food legume crop that is ranked third amongst legumes after dry bean (Phaseolus vulgaris) and field pea (Pisum sativum) (Mubvuma, 2018). The crop is cultivated in semiarid tropical and subtropical regions of the world (Sadras & Calderini, 2020) and interest in chickpea production is growing in many countries because of its uses as a source of livestock feed, human protein, fuel, and fertilizer (Fikre et al, 2020;Martinelli et al, 2020;Santos et al, 2021;Veisi et al, 2020;Mthulisi & Mcebisi, 2020). However, despite all the advantages, the average chickpea seed yield per hectare is very low and ranges from 0.6 to 2.3 t ha −1 in different parts of the world (FAO, 2021).…”
Section: Introductionmentioning
confidence: 99%